Traffic matrix-based load balancing routing in flow-based smart identifier network - ARu JI; Shuai GAO; Hong-bin LUO; Hong-ke ZHANG; Ming WAN (Tongxin xuebao)
Smart identifier network (SINET)has an advantage of being aware of the accurate traffic matrix. Traffic ma-trix was use as the constraint, model on load balancing routing problem, and transform the primal problem into dual problem by using Lagrange function. Therefore,the optimization goal of the dual problem can be easily achieved. In or-der to achieve the dual problem optimization goal,a traffic matrix based load balancing routing algorithm (TM-LB)was proposed. By performing the TM-LB,the control plane can plan paths for subsequent traffic according to network fluctu-ation. OMNET++ was used to run the experiment simulation based on NSFnet topology. The results show that TM-LB can better reduce congestion and realize load balancing, compared with traditional routing mechanism. Finally, a proof-of-concept was built implementation and carry out experiments for testing the overhead of TM-LB algorithm.